Associação do hidróxido de cálcio e metronidazol no tratamento de dentes de cães com lesão periapical crônica - Barioni, Sônia Regina Panzarini [UNESP]; Souza, Valdir [UNESP]; Holland, Roberto [UNESP]; Dezan Junior, Eloi [UNESP] (FapUNIFESP (SciELO), 2006)
One of the primary objectives of endodontic treatment of teeth with pulp necrosis is the elimination of microorganisms from the root canal system, as effectively as possible, especially in cases with chronic periapical lesions. AIM: The purpose of this study was to analyze the response of the periapical tissue of dogs' teeth with chronic periapical lesions to endodontic treatment performed with utilization of metronidazole, calcium hydroxide, and an association of both as root canal dressings. METHODOLOGY: Forty root canals were submitted to pulpectomy and the root canals were kept exposed to the oral environment for 6 months. Then, they were submitted to biomechanical preparation and divided into 4 study groups with 10 specimens: group I - no root canal dressing; group II - calcium hydroxide; group III - metronidazole; group IV - calcium hydroxide associated to metronidazole. After 15 days, the root canals were filled with Fill Canal sealer. After 90 days, the animals were killed and the especimens processed for histological analysis. RESULTS: Calcium hydroxide dressing provided a significantly better outcome compared to other experimental groups (α = 0.01). Also, the results of the association of metronidazole and calcium hydroxide were similar to those observed for the metronidazole group. The worst results were obtained by the no root canal dressing group. CONCLUSION: The use of metronidazole alone or associated with Calcium hydroxide, did not improve periapical healing when compared to Calcium hydroxide dressing.
Association of calcium hydroxide and metronidazole in the treatment of dog's teeth with chronic periapical lesion
Keywords: Calcium hydroxide; Endodontic treatment; Metronidazole; Root canal dressing